Impact of integration of transferable skills into education and training on employability of women in Kenya: case for CAPYEI - Daniel Otieno; Jackline Nyerere; Christopher Shisanya; Wilson Mutuma; Damaris Kariuki; Hannah Bula; Shem Onsomo; John Macharia; Eldah Onsomu; Martha Muhwezi; Charles Ondieki; Jacqueline Onyango (Quality Education for All)
Purpose – This study evaluated a programme, CAP Youth Empowerment Institute (CAPYEI) that uses Basic Employability Skills Training (BEST) model to contribute the evidence and generate lessons on the type of skills needed to enhance women economic empowerment. The purpose of the study is to generate evidence of what works in women skill acquisition and employability in Kenya. Design/methodology/approach – This study adopted a mixed research design incorporating both quantitative and qualitative approaches to conduct an impact evaluation of the CAP YEI training programme on the employability and entrepreneurship of women and girls in Kenya. The design allows for the consideration of two groups: treatment and control groups thus allowing for a clear comparison of outcomes between those who received the training (treatment group) and those who did not (control group). Project evaluation data were collected from both primary and secondary sources. Given that the study was conducted post evaluation, it did not have baseline survey data, therefore an ex post baseline evaluation using a retrospective approach was computed. In the absence of a true baseline, the questionnaire was tailored to allow beneficiary recall. A key design consideration of impact evaluation study was the identification of a valid control group that could generate a suitable counterfactual outcome. Findings – The results indicate positive self-evaluation on most of the selected soft skills. For instance, over 80% of both the beneficiaries and non-beneficiaries indicated that they possessed communication, teamwork, interpersonal, decision-making, prioritization, assertiveness and negotiation skills, whereas 58 % and 63 % of the beneficiaries and non-beneficiaries, respectively, indicating that they possessed information and communication technology (ICT) skills. Results indicate that skills development improves chances of employment among the target group and especially women. The results indicate that addressing gender inequality requires targeted interventions. The targeted interventions could be aimed at ensuring that women and girls are empowered to compete favourable with men and boys in the labour market. Research limitations/implications – This study was an evaluative study of the impact of an intervention in a single case study. This means while the findings of the study are relevant to policy and practice, they cannot be generalized to a broader populace. The absence of base-line data rendered the use of comparative data impossible. Data generated through self-reported assessment of intervention impacts are prone to responder biases, which may raise questions about the validity of the findings. Practical implications – This study recommends integration of transferable skills training in teaching and training institutions to enhance competitiveness, employability and entrepreneurship chances of the graduates in the labour market. The study is significant in informing policy direction in Kenya. Originality/value – This study evaluated a model of integrating transferable skills into a young women training programme and evaluated its impacts with a view of documenting what works for women employability. This case is a unique one in the country specific context.